Creation of WebQuests for Cultural Education and Refugee Integration in Germany: On the Example of Cologne - Nalyvaiko, Oleksii; Ronzhes, Olena (Освітні виклики, 2023)
Purpose. This research aims to determine the methodology of creating and conducting web quests for people who have left their homes and settled in another country (especially emigrants and refugees). The study includes a clear definition of the sequence of creation and implementation of web quests for families who emigrated to Germany.Methodology. The research was conducted in the format of a single case study with a description of the creation of a specific web quest for a seed audience of emigrants and refugees. The methodology presented in the study included a description of the process, principles and means necessary for the organizer and other interested parties in case of reproduction of this web quest for a similar audience and in similar conditions.Results. The main results presented in the study include a clear algorithm for conducting the WebQuest “Family creative and educational quest in Cologne”, aimed at cultural adaptation and education in the field of history and iconic places of Cologne; «excursion program»; communication between different generations of families; a simple divergent task, proposed at each station of the WebQuest to creatively reinterpret the received excursion information; increasing the level of digital literacy.The article provides recommendations for increasing the effectiveness of WebQuest in the context of cultural adaptation of refugees and emigrants living in Germany.Conclusions. It was determined that creating and conducting WebQuests is a complex and time-consuming process, the goal of which is to maximize interactivity and involvement of participants. Therefore, the creators of such a digital product need to consider a number of features of the participants and digital tools used in the process. The format of web quests allows people to involve their whole family with the process, which significantly increases their cohesion in a new place and enables integration and adaption with not solely individual family members, but the whole family, which expands the level of awareness of the culture and history of their new home.